LUNG TISSUE MORPHOLOGY IN CHEMOTHERAPY (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
According to statistics, breast cancer is the leading cause of cancer in women. Chemotherapy is a chemical method, a method of treatment with drugs that have an anti-malignant effect. Drugs used in chemotherapy cause various changes in the lungs. Lung damage in chemotherapy is one of the most urgent problems of oncology in cancer patients. Therefore, this study investigated the morphological changes that occur in lung tissue as a result of chemotherapy for breast cancer.